RELATIONSHIP OF THE STATE OF BIOMEMBRANES WITH INDICATORS OF ENDOTHELIUM DYSFUNCTION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - A. M. SABUROVA; KH.R. NASYRDZHANOVA; KH.YO. SHARIPOVA (Паёми Сино, 2020)
Objective: Examination the relationship between the state of biomembranes and indicators of endothelial dysfunction in patients with chronic obstructive pulmonary disease (COPD).